The Influence of Accounting Knowledge and Capital Adequacy on Financial Report Quality in Small and Medium Enterprises in Pancoran Mas District, Depok City - Hendarsih, Ida; Widajita, Ayu Dinaria; Martanti, Amas Sari; Tambunan, Diana; Santosa, Jaka (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The quality of financial reports is essential information for producing high-quality financial statements, which are valuable to both companies and business practitioners. This study aims to examine the effects of accounting comprehension and capital adequacy on the quality of financial reports, both individually and simultaneously, for small and medium-sized enterprises (SMEs) in Pancoran Mas District, Depok City. This quantitative research used a random sampling technique by distributing questionnaires to respondents, resulting in a sample of 76 participants. Data analysis was conducted using SPSS Version 26. The partial analysis results indicated a significance value of 0.00 < 0.05 for accounting comprehension, showing its influence on financial report quality, while the capital adequacy variable had a significance value of 0.037 < 0.05, indicating its impact as well. The F-test yielded a significance level of 0.000 with an F-calculated value of 24.642, compared to an F-table value of 3.12, where sig < 0.05 and F-calculated > F-table. Thus, it can be concluded that accounting comprehension and capital adequacy have a simultaneous effect on the quality of financial reports. Therefore, it can be said that SMEs with strong accounting understanding and sufficient capital are likely to produce high-quality financial reports.